The impact of intravenous fluid and electrolyte administration on total fluid, electrolyte and energy intake in critically ill adult patients - Veldsman, Lizl (Stellenbosch : Stellenbosch University, 2013)
Thesis (MNutr)--Stellenbosch University, 2013.